Play dead - Mason, Jane B.; Hines-Stephens, Sarah (New York : Scholastic, 2013)
Retired police dog Dodge and his girl Cassie are always ready for a new mystery, so when the richest man in town disappears without a trace and without a will, Dodge and Cassie are on the case, but the clues lead to something more sinister than a missing millionaire.
Publisher's Weekly, December 2012
3.3
3-6
3-6
Publisher's Weekly
550
Keywords: Police dogs -- Juvenile fiction; German shepherd dog -- Juvenile fiction; Teenage girls -- Juvenile fiction; Missing persons -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Police dogs -- Fiction; German shepherd dog -- Fiction; Dogs -- Fiction; Teenage girls -- Fiction; Missing persons -- Fiction; Human-animal relationships -- Fiction; Mystery and detective stories; Police dogs -- Fiction; Dogs -- Fiction; German shepherd dogs -- Fiction; Girls -- Fiction; Teenagers -- Fiction; Missing persons -- Fiction; Human-animal relationship -- Fiction; Mystery fiction; Mystery fiction